2004
DOI: 10.1080/00107510310001632523
|View full text |Cite
|
Sign up to set email alerts
|

Black holes and information theory

Abstract: During the past three decades investigators have unveiled a number of deep connections between physical information and black holes whose consequences for ordinary systems go beyond what has been deduced purely from the axioms of information theory. After a self-contained introduction to black hole thermodynamics, we review from its vantage point topics such as the information conundrum that emerges from the ability of incipient black holes to radiate, the various entropy bounds for non-black hole systems (hol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 53 publications
2
85
0
Order By: Relevance
“…i.e., α < 8πνζ [14,15,16]. Hence the candidate with R 1 = R max (E 1 ) cannot have very large α values, and is not an HEO as defined here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…i.e., α < 8πνζ [14,15,16]. Hence the candidate with R 1 = R max (E 1 ) cannot have very large α values, and is not an HEO as defined here.…”
Section: Introductionmentioning
confidence: 99%
“…This made possible an alternative argument for a bound on a weakly self-gravitating object's entropy which is just a factor of O(10) above (2) [14,15,16]. In the new argument the object is dropped from such a distance that the energy drawn from the hole by the Hawking radiance during the whole infall is balanced by the energy (at infinity) brought in by the object-the BH is left unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Further, information processing may play a fundamental role in our understanding of physical laws [5,6,7,8]. Conversely, the discovery of Shor's algorithm [9] suggested that knowledge of the physical world is relevant to study the limits of efficient computation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, this quantity and its derivatives are used to discuss of black holes, questions connected with the accelerated expansion of the Universe, to build and generalize gravitation theories, etc. (see, e.g., [6][7][8][9][10]). The majority of the papers, being strictly theoretical, place principal emphasis on functional relations between variables established through the analysis of entropy and its production.…”
Section: Introductionmentioning
confidence: 99%